74‐3: Image Deblurring of Camera Under Display by Deep Learning. Issue 1 (25th September 2020) - Zhang, Zhenhua
Abstract : A deep learning method is provided in this paper to deblur images captured behind OLED screen named Camera Under Display (CUD). Because of optical diffraction of OLED pixel pattern, images captured by front camera under the display panel are unfavorably blurred. This paper proposed a modified GAN training network to deblur these images, with result showing perceptually clearer image with better restored high spatial frequency information.